Magnetism in non-stoichiometric goethite of varying total water content and surface area (2006)
ABSTRACT: In this work, the magnetic properties of four non-stoichiometric goethites with varying total water content and surface area have been investigated. The samples were prepared using two different hydrothermal methods, deriving either from Fe(II) precursors or from Fe(III) precursors. The effects of both agitation during mixing solutions and drying time during synthesis upon the physical properties of the final products were also studied. The samples were characterized by XRD, TGA, BET, Fe M¨ossbauer spectrometry at 300 K, 77 K and 4.2 K, ZFC and FC curves, and magnetization curves. The goethites synthesized from the Fe(II) precursors result less crystalline, contain higher water content than those prepared from the Fe(III) precursor. In addition, ferrous precursor goethites exhibit superparamagnetic relaxation effects, while the ferric precursor goethites exhibit magnetic ordering of clusters. It is found that the stirring process during synthesis can affect the total water content and the magnetic behaviour of the goethites. Our results suggest that structural water content decreases the magnetic hyperfine field at 4.2 K. The adsorbed water content also affects this parameter as suggested by in situ annealing cycles of the goethites in a M¨ossbauer cryofurnace. Finally, we propose an unique 2-D phase diagram to describe all the magnetic properties of present goethites observed as a function of temperature, surface area (or particle size) and total water content.